Numerical study on the design and performance of cathode flow channels in solid oxide fuel cells based on bionic airfoil structures - Lirong Fu; Xuan Fang; Jinyi Liu; Mingwei Li (Fuel, 2026)

Integrating dynamic vegetation phenology into SWAT improves watershed nitrogen and phosphorus simulations - Zheng Wang; Jianhua Liu; Mingwei Li; Jiahao Chen; Xuan Zhang; Fanghua Hao; Yongshuo Fu (Journal of Environmental Management, 2026)

Characteristics and expression of the BES1 transcription factors family in foxtail millet (Setaria italica) reveal its potential roles in drought stress responses - Xueyan Xia; Xiaohong Fu; Yu Zhao; Jihan Cui; Nuoya Xiao; Meihong Huang; Yiwei Lu; Jingxin Wang; Cheng Chu; Shunguo Li; Mingwei Ding (Cereal Research Communications, 2026)

Wave flow field design optimization for enhanced performance of high-temperature PEM fuel cells - Mingwei Li; Lirong Fu; Huadong Lin; Jinyi Liu; Xiaosong Zhang (Fuel, 2026)

Design and optimization of triply periodic minimal surface structure flow channels in proton exchange membrane fuel cells based on genetic algorithm - Lirong Fu; Yiwen Tang; Jinyi Liu; Mingwei Li; Na Qiu (Fuel, 2026)

Fireproof gel polymer electrolyte constructed by fluorine/phosphorus-contained polymer matrix for high-voltage and high-safety lithium metal batteries - Xuelian Fu; Mingyang Yang; Qichong Yuan; Mingwei Liu; Jing Hu; Tianyu Guan; Guangfu Luo; Yun Yan; Xingqun Liao; Xuefeng Gao; Zhouguang Lu (Chemical Engineering Journal, 2025)

Research on improving injection and production gas capacity based on integrated reservoir-well coupling model for gas storage - Yu Fu; Ganlin Yuan; Yong Xia; Mingwei Wang; Yunjun Zhang; Xufeng Yang; Zibo Wang; Yuxin Cheng (Fuel, 2025)

Chlorella-regeneration of exhausted D301-Zr nanocomposite adsorbent of phosphate sequestration from water: A multi benefits approach with adsorbent regeneration, phosphorus reuse, and carbon fixation - Mingwei Fu; Mingyang Lin; Sufeng Wang; Jingshan Li (Journal of Water Process Engineering, 2025)

Incorporating Drought Thresholds Improves Model Predictions of Autumn Phenology in Tropical and Subtropical Forests - Yue Xu; Mingwei Li; Zitong Jia; Yufeng Gong; Xiran Li; Yongshuo H. Fu (Global Change Biology, 2025)
Drought dramatically influences vegetation phenology, thereby impacting terrestrial carbon and water cycles. However, the mechanisms by which drought drives changes in autumn phenology remain unclear, hindering the accurate simulation of these processes in phenology models. In this study, we employed ridge regression analysis to quantify the dynamic effects of intensifying drought on the end‐of‐photosynthetic‐growing‐season (EOPS) and identified the drought threshold at which the vegetation's response to drought shifts. We demonstrate that the response of EOPS in tropical and subtropical forests reverses from a delay to an advancement as drought intensity surpasses specific thresholds, with the average drought threshold across the study area corresponding to a standardized precipitation evapotranspiration index (SPEI) value of −0.9. Drought thresholds, however, vary geographically, increasing along the precipitation gradient, potentially due to variations in drought stress‐related gene expression and tolerance strategies across different humidity environments. Therefore, we developed a new autumn phenology model (DMPD) by incorporating a drought threshold parameter that distinguishes contrasting drought effects and predicts future EOPS under two scenarios (SSP245 and SSP585). The DMPD model substantially enhanced the representation of EOPS, as evidenced by a lower root mean square error (RMSE), higher correlation, and a greater proportion of significant correlations with EOPS derived from GOSIF. By the end of the century, EOPS is projected to be consistently delayed under both moderate (SSP245) and high (SSP585) warming scenarios, with the rate of delay decelerating under SSP245 after 2066. Our study confirms that increasing drought intensity leads to contrasting shifts in the autumnal photosynthetic phenology of tropical and subtropical forests and highlights the potential of integrating these contrasting drought effects into phenology models to improve the accuracy of vegetation phenology predictions under future climate change scenarios.

Study on excitation effect of different combination modes of shear wave vibroseis - Zhengtao You; Zhiqiang Huang; Lei Hao; Gang Li; Mingwei Fu; Ruohao Wang; Jun Shuai (Acta Geophysica, 2025)

Neglected role of iron redox cycle in direct interspecies electron transfer in anaerobic methanogenesis: Inspired from biogeochemical processes - Hui Xu; Mingwei Wang; Shengqiang Hei; Xiang Qi; Xiaoyuan Zhang; Peng Liang; Wanyi Fu; Bingcai Pan; Xia Huang (Water Research, 2024)

Biomimetic anode with atomically dispersed iron sites to enhance biotic-abiotic interfacial interaction towards efficient wastewater energy recovery in bioelectrochemical systems - Mengxi Yin; Boya Fu; Tengfei Ren; Mingwei Wang; Xiaoxin Cao; Xia Huang; Xiaoyuan Zhang (Chemical Engineering Journal, 2023)

Risk assessment of Artemia egg shell-Mg-P composites as a slow-release phosphorus fertilizer during its formation and application in typical heavy metals contaminated environment - Sufeng Wang; Xiaojuan Lv; Mingwei Fu; Zijing Wang; Dan Zhang; Qina Sun (Journal of Environmental Management, 2023)

Metal-organic framework-derived one-dimensional Pd@CeO2 catalysts with enhanced activity for methane oxidation - Mingwei Wu; Meng Miao; Wenzhi Li; Xia Zhang; Lulu Zhang; Taimin Zhen; Yan Fu; Jingting Jin; Liang Yuan (Fuel, 2023)